EFFICACY OF EGG YOLK FROM THREE AVIAN SPECIES ON SEMEN FREEZABILITY OF THARPARKAR BULL - SINGH, MAHAK; RAMTEKE, SNEHAL S; GHOSH, S K; PRASAD, J K; RAJORIYA, J S (The Indian Journal of Animal Reproduction, 2023)
Egg yolk is one of the most widely used cryoprotective components for sperm preservation and a wide rangeof factors affect its action on sperm motility, viability and fertilizing ability. The aim of this experiment was todetermine the effect of different species egg yolk, namely the domestic chicken (Gallus domesticus), duck (Anasplatyrhynchos) and Japanase quail (Coturmixjaponica) on sperm quality following cryopreservation ofTharparkarbull semen. A total of 30 ejaculates from three bulls (1 O from each bull) were used in the experiment. Eachejaculate was divided into three equal parts and diluted with three different extenders with 20 per cent egg yolkfrom domestic chicken (Gallus domesticus) (CEY), domestic duck (Anas platyrhynches) (DEY) and Japanasequail (Coturnixjaponica) (QEY). The semen straws were equilibrated at4°C for4 hrs and freezing was done usingbiological cell freezer (-140°C) and stored in liquid nitrogen (-196 °C). After thawing (37°C for 30 s), sperm motility,viability, acrosomal integrity and membrane integrity (HOST) were evaluated. The post extension sperm motilitydid not differ among three extenders. Result of present experiment showed that QEY based tris extender hadbetter post-thaw motility, viability, acrosomal integrity and membrane integrity (HOST) (p
Keywords: Tharparkar bull; Semen; Cryopreservation; Egg yolk